2021
DOI: 10.1099/ijsem.0.004579
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium fessum sp. nov., isolated from human faeces

Abstract: An obligately anaerobic, Gram-stain-positive and spore-forming strain, SNUG30386T was isolated from a faecal sample of a healthy Korean subject. The strain formed a round ivory-coloured colony and cells were chained rods with tapered ends, approximately 2.0–2.5×0.6–0.8 μm in size. The taxonomic analysis indicated that strain SNUG30386T was within the family Lachnospiraceae . According to the 16S rRNA gene sequence similarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…1 ). The results showed that C5-48 T co-clustered with C. fessum SNUG30386 T [ 28 ] and L. edouardi Marseille-P3397 T [ 29 ], and this cluster was closely related to the Enterocloster cluster although these two strains were not previously considered to be strains of Enterocloster [ 8 ]. To further confirm the phylogenetic position of strain C5-48 T , we performed phylogenetic analysis based on the nucleotide sequences coding for the β subunit of RNA polymerase ( rpoB ) (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). The results showed that C5-48 T co-clustered with C. fessum SNUG30386 T [ 28 ] and L. edouardi Marseille-P3397 T [ 29 ], and this cluster was closely related to the Enterocloster cluster although these two strains were not previously considered to be strains of Enterocloster [ 8 ]. To further confirm the phylogenetic position of strain C5-48 T , we performed phylogenetic analysis based on the nucleotide sequences coding for the β subunit of RNA polymerase ( rpoB ) (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The fatty acid type such as C 14 : 0 or C *Data for C. manihotivorum CT4 T taken from [16]. [22,[63][64][65][66][67][68][69][70]. Characteristically, the fatty acids C 12 : 0 FAME, summed feature 1 and summed feature 6 were present in strain D1-1 T , but were absent in the type strains of the most closely related species C. zeae.…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%
“…thailandense , and C. beihaiense [22, 63–70]. Characteristically, the fatty acids C 12 : 0 FAME, summed feature 1 and summed feature 6 were present in strain D1-1 T , but were absent in the type strains of the most closely related species C.…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%
“…Recently renewed interest in the gut microbiome has led to the isolation and description of several new species and an increase in the composition of Lachnospiraceae taxa by ~50 % [7]. Members of the Clostridium cluster XIVa belonging to the family Lachnospiraceae have been classified into new genera such as Faecalicatena , Dorea , Coprococcus , Hungatella , Enterocloster , Lacrimispora , Anaerotignum , Roseburia , Butyrivibrio , Mediterraneibacter and Faecalimonas [8, 9]. Among these genera, a few species from the genus Faecalicatena were reclassified as Faecalicatena contorta , Faecalicatena fissicatena and Faecalicatena orotica [10].…”
Section: Full-textmentioning
confidence: 99%